PERAN NOTARIS PENGGANTI DALAM MENJALANKAN JABATAN NOTARIS YANG DIGANTIKAN DI WILAYAH KOTA YOGYAKARTA - BUSTAMI, FAURIKA KIKI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Research on The Role Of Subtitute Notary In Running The Post Of Notary Who Supplanted In Yogyakarta City Area aimed to review the role of subtitute notary in carrying the post of notary who supplanted, responsibility of subtitute notary against protocol that is given by notary who supplanted, and the constraints that have been faced by subtitute notary in carrying out the post of notary who supplanted. Research conducted is normative empirical research, in which data obtained from libraries research and supported by field research, done with interview. The sample collection technique used is non random sampling or non probability sampling, while the type of the sample used is purposive sampling. The subject of the study consisted of 14 respondents, namely 6 notary who never leave of absence, and 8 people once served a notary a subtitute for. The overall data obtained was analyzed qualitatively and presented in the form of descriptive. The results showed that the use of the leave entitlement of notary public could cause lacunae in public serving against an authentic deed. Therefore, subtitute notary have a very important role, which is continuing the post of notary who supplanted, pertaining to the protocol of notary and public need against an authentic deed. Before performing the post of notary, subtitute notary also lifting the oath of office, as well as a notary, so that as a consequence subtitute notary must be responsible morally and legally, either to the state and to the public. Constraints that have been faced by substitute notary in running his term of office, among others lack of experience of subtitute notary, limited capability of subtitute notary, and the existence of doubts from prospective clients against subtitute notary.